Missionêre perspektiewe op Teologiese opleiding - J.J. Kritzinger (Verbum et Ecclesia, 2001)
In the light of the transformation in society and in tertiary education, renewed attention should be given to the church, its mission, and the mission of its theological schools. If it were true that the church is the Body of Christ, called to continually be involved in God's outreach to his world, then the training of missionaries and the place of mission in the theological curriculum should also receive renewed attention. The author re-iterates the need for both a focused Missiology and the development of a true missionary theology in the theological faculty. He also indicates a need for academic Missiology to become involved in the training of missionaries.